Marginal deformations and RG flows for type IIB S-folds - Arav,I; Gauntlett,JP; Roberts,MM; Rosen,C (The Journal of High Energy Physics, 2021)
We construct a continuous one parameter family of AdS4 × S1 × S5 S-fold solutions of type IIB string theory which have nontrivial SL(2, ) monodromy in the S1 direction. The solutions span a subset of a conformal manifold that contains the known N = 4 S-fold SCFT in d = 3, and generically preserve N = 2 supersymmetry. We also construct RG flows across dimensions, from AdS5 × S5, dual to N = 4, d = 4 SYM compactified with a twisted spatial circle, to various AdS4 ×S1 ×S5 S-fold solutions, dual to d = 3 SCFTs. We construct additional flows between the AdS5 dual of the Leigh-Strassler SCFT and an N = 2 S-fold as well as RG flows between various S-folds.